Chemical Differences Between Voided and Bladder Urine in the Aye‐Aye (Daubentonia madagascariensis): Implications for Olfactory Communication Studies. Issue 7 (1st October 2012) - DELBARCO‐TRILLO, JAVIER; HARELIMANA, INNOCENT H.; GOODWIN, THOMAS E.; DREA, CHRISTINE M.; Higham, James P.; Semple, Stuart
<x xml:space="preserve">Abstract</x> Urine serves a communicative function in many mammalian species. In some species, the signaling function of urine can be enhanced by the addition of chemical compounds from glands along the distal portion of the urogenital tract. Although urine marking is the main mode of chemical communication in many primate species, there has been no study of the contribution of urogenital secretions to the chemical complexity of primate urine. Here, we compared the chemical composition of bladder urine versus voided urine in the aye‐aye, Daubentonia madagascariensis, a strepsirrhine primate that relies on urine in intraspecific communication. Both types of urine, collected from each of 11 aye‐ayes representing both sexes of varying adult ages, underwent headspace analysis via gas chromatography and mass spectrometry. Although the average number of compounds was similar in bladder and voided urine, 17% of the compounds detected occurred exclusively in voided urine (but only in a subset of individuals). An overall measure of chemical complexity (using a nonmetric multidimensional scaling analysis) showed that both types of urine were chemically different at the individual level. There was no apparent sex or age differences in the chemical components found in aye‐aye urine. Nonetheless, the individual dissimilarities between bladder urine and voided urine indicate chemical contributions from structures along the urogenital tract and offer further support for the relevance of urinary communication in the aye‐aye. Am. J. Primatol. 75:695‐702, 2013. © 2012 Wiley Periodicals, Inc.